Cincoriola Haque from Dhak Pass Formation, Surghar Range, District Mianwali, Pakistan - Raza, Syed Mahmood (Journal of Himalayan Earth Sciences, 1970)
Haque (1956), described a new genera Cincoriola (pro Punjabia) and its two species, viz., C. ovoidea and C. patalensis from the upper horizons of the Patala Formation in Nammal Gorge, western Salt Range, Pakistan. The present investigation has recorded for the first time a rich assemblage from the Dhok Pass Formation in Lumshiwal Nala, Surghur Range, which is the oldest lithostratigraphic unit of the Paleocene Series in the region. Cincoriola patalensis Haque and a new species C. sp. A is described. This genus is proved to be a good time indicatrix for the Paleocene Epoch.